QARAQALPAQ TILINDE MIYWE-PALÍZ EGINLERINE BAYLANÍSLÍ KÁSIPLIK SÓZLERDIŃ LINGVOGEOGRAFIYALÍQ SÍPATLAMASÍ - Kaypnazarova, M.K. (SCIENCE and SOCIETY, 2025)
The article discusses the use of fruit and melon terms in the Karakalpak language. Examples are given of the peculiarities of fruit and melon crop names in the dialects of the Karakalpak language, and the linguogeographical description of the boundaries of their usage is reflected in dialectological maps.